New Attorney Swearing-In Ceremony in Exhibit (Valdez) Hall - Watkins, Howard::::::::: (1983)
Judges and Justices on dais facing new attorneys taking oath; Judge John 'Nip" Gallagher, Justices Charles Hamlin, Ken Andreen, Pauline Davis Hanson, Donald Franson, Presiding Justice George Brown, Justice George Zenovich, Justice Wickson Woolpert, Justice Robert Martin, U.S. District Court Judge M.D. Crocker